A COMPARATIVE ANALYSIS OF READING COMPREHENSION ABILITIES BETWEEN CHILDREN WITH DOWN SYNDROME AND TYPICALLY DEVELOPING PEERS - Aila Amir; Muhammad Eesa; Syeda Malika Batool; Zerkaish Fatima (International Journal of Contemporary Issues in Social Sciences, 2024)
This research study focused on investigating the reading comprehension skills of children with Down syndrome compared to typically developing children. The research utilized various standardized tests and assessments, including the Woodcock-Johnson Tests of Achievement, Test of Reading Comprehension, One Minute Reading Test, and Gray Oral Reading Test. The interactive compensatory model of linguistics was applied as a theoretical framework for data analysis. The sample consisted of five children with Down syndrome and five typically developing children matched for age and gender. The assessments covered areas such as word recognition, decoding, vocabulary, comprehension strategies, critical thinking, and reading fluency. The data obtained from the pre- and post-tests were analyzed to determine the performance levels and improvements in reading comprehension skills over a period of three months. The results indicated that children with Down syndrome showed significant improvements in their reading comprehension abilities after the intervention.